Determinanty zmian deficytu budżetu państwa i długu publicznego w krajach Unii Europejskiej w 2010 roku - Malinowski, Dariusz (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2012)
The article contains an analysis of the budget deficit variability and public debt variation in the EU in 2010. Comparing the scale and economic determinants of changes in the state budget deficit and public debt in 2010 in the Central and Eastern European EU member states and in other EU countries we reach the following conclusions: 1) The average scale of the improvement of the economic result of the state budget as % of GDP was higher in the Central and Eastern Europe countries comparing to other EU member states. In the first group of countries, economic results improved on average by 1.1 percentage points, and in the other by 0.75 percentage points. 2) In most Central and Eastern European countries, as well as in most other EU countries the decline in budgetary expenditure, expressed in% of GDP was the only or major determinant of the reduction of the economic deficit of the state budget as % of GDP. Reduction of public spending in GDP was in turn the result of reducing the fiscal growth of nominal spending. In the Central and Eastern European countries in 2010, the nominal budget spending, decreased on average by 0.4%, while in 2009 increased on average by 16.1%. 3) In the rest of the EU average increase in public debt as % of GDP was higher than the average increase in public debt in the countries of Central and Eastern Europe. For the rest of the EU member states, public debt at the end of 2010 as % of GDP was by 4.65 percentage points higher than at the end of 2009, and for the Central and Eastern European countries by 4.14 percentage points higher. At the end of 2010 Central and Eastern European countries had significantly lower average level of public debt as % of GDP in comparison with other EU members states (38.9% of GDP and 74.8% of GDP). In most other EU countries there is virtually no limit for increasing the public debt, therefore there is no limit for a high budget deficit. Among Central and Eastern European EU member states only Hungary are in similar situation while Poland is close by. Therefore, most other EU countries and some countries of Central and Eastern Europe must immediately substantially reduce the scale of the economic deficit of the state budget. Countries where public debt is relatively low should not delay further restrictions of the state budget deficit as later on they will have to make this reduction under pressure of time. Above else, high economic deficit negatively impacts the economy, including economic growth. If EU member states fail to implement quickly the low economic state budget defi cit policy, they will plunge into economic recession that will last for many years.